State Policies on Religious Freedom in Indonesia: Decolonial Perspectives, Historical Contexts, and Contemporary Challenges - Aziz Maulana, Fauzan; Ding Changchun (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This study examines state policies on religious freedom in Indonesia through decolonial perspectives, analyzing how colonial legacies continue to shape contemporary religious governance despite constitutional guarantees of pluralism. Using qualitative methods through extensive literature review, this research traces the evolution of religious policies from pre-independence through the Sukarno and Suharto periods to the post-Reformasi decentralization era, revealing how postcolonial nationalism has reproduced rather than transcended colonial patterns of categorizing, surveilling, and controlling religious diversity. The findings demonstrate that systematic discrimination against minority groups, particularly Ahmadiyah and Shia communities, represents not merely policy implementation failures but structural continuities with colonial governmentality that renders certain religious expressions illegitimate. Through case studies of violence in Cikeusik and Sampang, regional discriminatory regulations, and the closure of houses of worship, this research illuminates how decentralization has paradoxically enabled both local accommodations and new forms of majoritarian control. While Indonesia's historical, political, and cultural contexts have shaped its approach to religious diversity and tolerance, the practical implementation of constitutional rights often faces significant challenges rooted in colonial epistemologies. The study argues that achieving genuine religious freedom requires comprehensive decolonization—transforming epistemological frameworks, dismantling discriminatory legal structures, reforming religious education, and supporting civil society resistance—rather than merely technical policy adjustments within inherited colonial-postcolonial frameworks, thereby addressing persistent issues of pluralism and intolerance that continue to affect religious minorities.